Green Innovation and Competitive Advantage: Empirical Evidence from Manufacturing Industries - Yuneka Saristiana; Fendy Prasetyawan; Anggun Wida Prawira; Ali Anhar Syi’bul Huda (International Journal of Economic and Business Research, 2026)
Green innovation has become a critical strategic mechanism through which manufacturing firms pursue competitive advantage amid increasing environmental and market pressures. This study aims to examine how green innovation contributes to competitive advantage in manufacturing industries by synthesizing empirical evidence from existing scholarly literature. Employing a qualitative, literature-based research approach, the study systematically reviews and analyzes peer-reviewed studies addressing green product innovation, green process innovation, organizational capabilities, and institutional drivers of competitiveness. The findings reveal that green innovation positively influences competitive advantage by enhancing differentiation, efficiency, adaptability, and market legitimacy. Moreover, the sustainability of these competitive gains is strongly shaped by complementary organizational factors such as green human resource practices, intellectual capital, dynamic capabilities, research and development investment, and supply chain integration. The study concludes that green innovation functions as a systemic strategic asset rather than an isolated environmental practice. These results contribute to the theoretical understanding of sustainability-driven competitiveness and offer strategic implications for manufacturing firms seeking long-term competitive resilience